Insulin Therapy of Nondiabetic Septic Patients Is Predicted by para-Tyrosine/Phenylalanine Ratio and by Hydroxyl Radical-Derived Products of Phenylalanine. (20th October 2015) - Kun, Szilárd; Molnár, Gergő A.; Sélley, Eszter; Szélig, Lívia; Bogár, Lajos; Csontos, Csaba; Miseta, Attila; Wittmann, István
Abstract : Hydroxyl radical converts Phe to para -, meta -, and ortho -Tyr ( p -Tyr, m -Tyr, o -Tyr), while Phe is converted enzymatically to p -Tyr in the kidney and could serve as substrate for gluconeogenesis. Pathological isoforms m - and o -Tyr are supposed to be involved in development of hormone resistances. Role of Phe and the three Tyr isoforms in influencing insulin need was examined in 25 nondiabetic septic patients. Daily insulin dose (DID) and insulin-glucose product (IGP) were calculated. Serum and urinary levels of Phe and Tyr isoforms were determined using a rpHPLC-method. Urinary m -Tyr/ p -Tyr ratio was higher in patients with DID and IGP over median compared to those below median (P = 0.005 andP = 0.01, resp.). Urinary m -Tyr and m -Tyr/ p -Tyr ratio showed positive correlation with DID (P = 0.009 andP = 0.023, resp.) and with IGP (P = 0.004 andP = 0.008, resp.). Serum Phe was a negative predictor, while serum p -Tyr/Phe ratio was positive predictor of both DID and IGP. Urinary m -Tyr and urinary m -Tyr/ p -Tyr, o -Tyr/ p -Tyr, and ( m -Tyr+ o -Tyr)/ p -Tyr ratios were positive predictors of both DID and IGP. Phe and Tyr isoforms have a predictive role in carbohydrate metabolism of nondiabetic septic patients. Phe may serve as substrate for renal gluconeogenesis via enzymatically produced p -Tyr, while hydroxyl radical derived Phe products may interfere with insulin action.